2018
DOI: 10.1111/ans.14808
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations in the first extensor compartment: a cadaver study

Abstract: Our findings may help to improve the awareness of the anatomical variations in the first extensor compartment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…There can be supernumerary tendons or tendons with different points of insertion, contrary to descriptions in the classical literature (Testut et al, 1979;Bergman et al, 1984;O'Rahilly, 1986;Orts, 1987;Williams, 1995;Rouviere et al, 2005). These observations are supported by current evidence, which implies that the percentage of APL muscle variants can range from 33 % to 100 % (Lacey et al, 1951;Coleman et al, 1953;Baba, 1954;Jackson et al, 1986;Brunelli et al, 1991;Khoury et al, 1991;van Oudenaarde, 1991;Yuksel et al, 1992;Zancolli and Cozzi, 1992;Fabrizio et al, 1996;Dos Remédios et al, 2005;Shiraishi et al, 2005;Kulthanan et al, 2007;Paul et al, 2007;Mehta et al, 2009;Bravo et al, 2010;Roy et al, 2012;El-Beshbishy et al, 2013;Thwin et al, 2014;Tewari et al, 2015;Lee et al, 2017;Palatty et al, 2018;Xu et al, 2018;Karauda et al, 2020;Deivasigamani et al, 2021;Gnanasekaran et al, 2021). These data show that the presence of accessory or supernumerary APL tendons in human anatomy is not unusual and is rather common.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…There can be supernumerary tendons or tendons with different points of insertion, contrary to descriptions in the classical literature (Testut et al, 1979;Bergman et al, 1984;O'Rahilly, 1986;Orts, 1987;Williams, 1995;Rouviere et al, 2005). These observations are supported by current evidence, which implies that the percentage of APL muscle variants can range from 33 % to 100 % (Lacey et al, 1951;Coleman et al, 1953;Baba, 1954;Jackson et al, 1986;Brunelli et al, 1991;Khoury et al, 1991;van Oudenaarde, 1991;Yuksel et al, 1992;Zancolli and Cozzi, 1992;Fabrizio et al, 1996;Dos Remédios et al, 2005;Shiraishi et al, 2005;Kulthanan et al, 2007;Paul et al, 2007;Mehta et al, 2009;Bravo et al, 2010;Roy et al, 2012;El-Beshbishy et al, 2013;Thwin et al, 2014;Tewari et al, 2015;Lee et al, 2017;Palatty et al, 2018;Xu et al, 2018;Karauda et al, 2020;Deivasigamani et al, 2021;Gnanasekaran et al, 2021). These data show that the presence of accessory or supernumerary APL tendons in human anatomy is not unusual and is rather common.…”
Section: Discussionsupporting
confidence: 62%
“…Only Brunelli et al (1991) and van Oudenaarde (1991) reported their use, the latter in only 22 of their 84 samples. These two factors hinder proper comparison since intratendinous dissection could account for the supernumerary tendons recognised in the studies reviewed (Lacey et al, 1951;Coleman et al, 1953;Baba, 1954;Jackson et al, 1986;Brunelli et al, 1991;Khoury et al, 1991;van Oudenaarde, 1991;Yuksel et al, 1992;Fabrizio et al, 1996;Dos Remédios et al, 2005;Shiraishi et al, 2005;Kulthanan et al, 2007;Paul et al, 2007;Mehta et al, 2009;Bravo et al, 2010;Roy et al, 2012;El-Beshbishy et al, 2013;Thwin et al, 2014;Tewari et al, 2015;Lee et al, 2017;Palatty et al, 2018;Xu et al, 2018;Karauda et al, 2020;Deivasigamani et al, 2021;Gnanasekaran et al, 2021). Nonetheless, if the data were to be compared with the present study, the ranges observed would be similar with a mean maximum of five tendons and a two tendon APL being the most frequent pattern.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The number of APL and EPB tendons is also associated with an increased risk of developing the disease (2). Moreover, these differences affect the success rate of different treatments (11,12). Understanding the anatomical variations of this compartment is essential for effective treatment.…”
Section: Introductionmentioning
confidence: 99%